PEMBELAJARAN KEBENCANAAN BAGI PENYANDANG DISABILITAS DI KABUPATEN KLATEN - Wirid Winduro (JI@P, 2017)
This research stemmed from the fact that the implementation of learning forstudents in the regency school in Klaten still less than optimal. After two yearsrunning since the policy was set, not all school organized learning about thedisaster. Scholls for children with disabilities in the sub district of Klatennumbered 12, nevertheles there was only one which carried out the learningabout the disaster, that was the YAAT School for disabilities. There wasambarrasing reality that the disabilities should be put attention, but in fact therewere neglected. This research used the collaboration of the theories of MerileeS. Grindle, GC Edward III and Van Meter-Van Horn for explaining the policyimplementation. Based on this theoretical collaboration there were eihgtindicators. The mentioned indicators were: policy content, policy context,policy output, communication, resources, implementator’s attitude,bureaucratic structure, and external factor. Based om case study at disabilityschool type A at YAAT indicated that the disability shools were not theprioritized target group. Learning about disaster were able to be accomplshedat YAAT since there were pushing synergic other factors; i.e. social as well aseconomic factors. Other supporting factors were policy context, disposition,communication, organizational structure, resources, and implementators’understanding toward the content and policy output.Key words: policy content; policy context; policy output; communication; resources;disposition; bureaucratic structure; external factor.